High-temperature flow behaviour of grain-oriented and non-grain-oriented electrical steel. Issue 9 (13th June 2019) - Giri, Sushil K.; Durgaprasad, A.; Thool, K.; Kundu, S.; Samajdar, I.
ABSTRACT: Plane strain compression tests were performed on grain-oriented (GO) and non-grain-oriented steel specimens of identical silicon content. Though Arrhenius type constitutive equations showed excellent predictability of the experimental flow stresses, there were clear differences in the flow curves of the respective grades. More specifically, GO steel had higher flow stress and work hardening and showed clear presence of dynamically recrystallized grains. All these were attributed to the higher (0.06 versus 0.003  wt-%) carbon content and corresponding presence of austenite, at elevated temperatures, in the GO steel specimens.